Temporal and Spatial Changes of Dust Aerosol over Qinghai-Xizang （Tibet） Plateau and Analysis on Its Source Regions - Bentao LI; Lei ZHANG; Yunshu ZHANG; Haotian ZHANG; Gefei LU (Gaoyuan qixiang, 2023)
Dust aerosol is an important component of the Earth's atmospheric aerosols， and has essential impacts on global climate， ecological environment and human body health.The spatial and temporal distributions of dust aerosol and their variations over Qinghai-Xizang （Tibet） Plateau are of great significance to be further investigated and estimated for evaluating the climatological and environmental effects of dust aerosol loading over Qinghai-Xizang （Tibet） Plateau.In this study， based on the data from different sources， including FengYun （FY） geostationary satellite remote sensing data and re-analysis data， both spatial and temporal characteristics of dust aerosol over Qinghai-Xizang （Tibet） Plateau are counted and analyzed within the period from 1999 to 2020.The intensity of dust activity over Qinghai-Xizang （Tibet） Plateau during monsoon period is stronger than that during non-monsoon period.More specifically， multi-year averaged seasonal aerosol optical depths （AODs） are 0.176， 0.064， 0.032 and 0.060， while dust optical depths （DODs） achieve 0.223， 0.118， 0.069 and 0.117 for spring， summer， autumn and winter.The dust activity is most active over Qaidam Basin， and small scale and isolated dust occurrences are also observed over the southern and western Qinghai-Xizang （Tibet） Plateau.The number of days， in which it is occurred with dust event， is 192， 218 and 212 from 2018 to 2020， respectively.The dust sources in East Asia （about 62%）， and Middle East and Central Asia （about 30%） are the main sources of dust aerosols for the northern and southern TP， separately.The dust originating from North Africa， mainly affects high-elevation regions in the southern Qinghai-Xizang （Tibet） Plateau.The intensity of dust activity over Qinghai-Xizang （Tibet） Plateau is relatively strong from 2000 to 2012， but its trend turns to be fluctuating from 2012 to 2020.The intensity and influencing area of dust activity over Qinghai-Xizang （Tibet） Plateau are both affected by variations of precipitation and wind over Taklamakan Desert， whose correlation coefficients with dust activity over Qinghai-Xizang （Tibet） Plateau are -0.56 and -0.32.